Desain Program Pendidikan Agama Kristen bagi Pemuda di Masa Pandemi dan Pasca Pandemi Covid-19 - Sozawato Telaumbanua (Jurnal Shanan, 2021)
Youth is the next generation of the nation and the church. However, in the midst of the Covid-19 pandemic, young people did not escape the impact caused by this Covid-19. Some youths experience stress in attending online schools/lectures, stress due to losing their jobs due to termination of employment by the company where they work, bored because they spend more time at home and rarely meet their peers, rarely meet community members church, even they are forced to only worship from home. Not a few youths have experienced a decline in spirituality during this pandemic. The church as a community of believers must be present and answer the needs of the youth who are experiencing the impact of the Covid-19 pandemic. In the midst of limitations during this pandemic, churches can attend and maximize service to youth through program designs that can answer their needs. Of course the church can take advantage of the technology that is currently developing so that services to youth, both during the pandemic and post-pandemic, continue to run. Therefore, through this article the author offers a design of a Christian religious education program for youth, in which youth can praise God together, share testimony and pray together. To answer the youth problems mentioned above, in writing this article the author uses qualitative research methods, namely comparing various literatures, be it books, articles, or journals related to the above discussion. The purpose of this paper is to offer a design of Christian religious education programs for youth during the Pandemic and Post-Pandemic. This program is expected to answer the needs of the youth as well as equip them through the light of God's word so that these youths remain rooted, grow and bear fruit in Christ in all circumstances.